Convenient microfluidic cartridge for single-molecule droplet PCR using common laboratory equipment. Issue 8 (3rd February 2021) - Takahara, Hirokazu; Matsushita, Hiroo; Inui, Erika; Ochiai, Masashi; Hashimoto, Masahiko
Abstract : A novel microfluidic cartridge eliminates the need for careful and time-consuming manual droplet handling using a micropipette, which is usually necessary for the transfer of droplets between the three discrete steps of droplet PCR. Abstract : We have previously established a cost-efficient in-house system for single-molecule droplet polymerase chain reaction (PCR) using a polydimethylsiloxane microfluidic cartridge and common laboratory equipment. However, the microfluidic cartridge was only capable of generating monodisperse water-in-oil droplets. Therefore, careful and time-consuming manual droplet handling using a micropipette was required to transfer droplets between the three discrete steps involved in the workflow of droplet PCR— i.e., (1) droplet generation; (2) PCR amplification; and (3) determination of the fluorescence intensity of the thermocycled droplets. In the current study, we developed a new microfluidic cartridge consisting of four layers, with a thin glass slide as the bottom layer. In this cartridge, droplets generated in the uppermost polydimethylsiloxane microfluidic layer are delivered to the glass slide in an online fashion. After the accumulation of many droplets on the glass slide, the cartridge is placed on the flatbed heat block of a thermocycler for PCR amplification. Direct fluorescence imaging of the thermocycled droplets on the glass slide is then carried out using a conventional fluorescence microscope. Efficient heat transfer from the heat block to the settled droplets through the thin glass slide was confirmed by successful PCR amplification inside the droplets, even from single template molecules. The new cartridge eliminates the need for manual droplet transfer between the major steps of droplet PCR analysis, allowing more convenient single-molecule droplet PCR than in our previous studies.